2017
DOI: 10.1111/nmo.13112
|View full text |Cite
|
Sign up to set email alerts
|

A role for interleukin 17A in IBD‐related neuroplasticity

Abstract: These findings identify IL-17A as a potential mediator of neuroanatomical remodeling of the gut innervation during IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…The loss of sympathetic fibers in the gut, as shown in the DSS colitis model, and also in specimens from patients with CD, is associated with increased expression of sympathetic repellents like semaphorin 3C and might result in reduced local inflammation control [28]. Sympathetic Nervous System and Chronic Inflammation However, using a DSS regimen in mice and TNBS regimen in rats, which leads to less severe colitis, even shows an increased growth of sympathetic axons, which may be mediated by the proinflammatory cytokine IL-17A [70,71]. Integrating both results, it seems that the balance between repellents like semaphorin 3C and sympathetic growth-promoting factors like IL-17A or nerve growth factor determines local sympathetic nerve density, leading to severely inflamed tissue without sympathetic neuronal control and areas of milder inflammation where central sympathetic control mechanisms might still be intact.…”
Section: And Below)mentioning
confidence: 99%
“…The loss of sympathetic fibers in the gut, as shown in the DSS colitis model, and also in specimens from patients with CD, is associated with increased expression of sympathetic repellents like semaphorin 3C and might result in reduced local inflammation control [28]. Sympathetic Nervous System and Chronic Inflammation However, using a DSS regimen in mice and TNBS regimen in rats, which leads to less severe colitis, even shows an increased growth of sympathetic axons, which may be mediated by the proinflammatory cytokine IL-17A [70,71]. Integrating both results, it seems that the balance between repellents like semaphorin 3C and sympathetic growth-promoting factors like IL-17A or nerve growth factor determines local sympathetic nerve density, leading to severely inflamed tissue without sympathetic neuronal control and areas of milder inflammation where central sympathetic control mechanisms might still be intact.…”
Section: And Below)mentioning
confidence: 99%
“…While it is unknown what factors control these processes, cytokines such as IL-17A could have a significant role. IL-17A induces the outgrowth of sympathetic neurons in the colon (48) and cultures from the SMG (54), although this has not been shown in secondary lymphoid organs, including the spleen. This role is also complicated by the ability of neurons to direct formation of lymphoid tissues during development and infection.…”
Section: A Innervation Of the Spleenmentioning
confidence: 99%
“…Prior three-dimensional imaging studies of mouse ileum revealed TH ϩ axons in the submucosa, with some, albeit sparse innervation in the macrophage rich mucosa (87). This sparse innervation in the naive mice does not seem to be static, with DSS-induced inflammation increasing the density of sympathetic axons in the colonic lamina propria (48). As an additional complication, tissue resident macrophages are phenotypically distinct from inflammatory monocyte-derived macrophages that have been recruited to a site of inflammation.…”
Section: A Neural Modulation Of Intestinal Immune Functionmentioning
confidence: 99%